2012
DOI: 10.1016/j.jnutbio.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with low-dose resveratrol reverses cardiac impairment in obese prone but not in obese resistant rats

Abstract: We hypothesized that a low-dose resveratrol will reverse cardiovascular abnormalities in rats fed a high-fat (HF) diet. Obese prone (OP) and obese resistant (OR) rats were fed an HF diet for 17 weeks; Sprague-Dawley rats fed laboratory chow served as control animals. During the last 5 weeks of study, treatment group received resveratrol daily by oral gavage at a dosage of 2.5 mg/kg body weight. Assessments included echocardiography, blood pressure, adiposity, glycemia, insulinemia, lipidemia, and inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 49 publications
4
42
1
2
Order By: Relevance
“…Similar results were reported by Kim et al (2011) andCho et al (2012). Albeit not all studies confirm that RSV reduces body fat (Louis et al, 2011;Tauriainen et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were reported by Kim et al (2011) andCho et al (2012). Albeit not all studies confirm that RSV reduces body fat (Louis et al, 2011;Tauriainen et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…The present study found similar results, that is, resveratrol supplementation increased IR, IRS1, and Akt phosphorylation in the myocardium and consequently, insulin sensitivity, as shown by the rate of glucose disappearance. Concordantly, resveratrol supplementation reduced hyperglycemia in an animal obesity model 25 .…”
Section: Discussionmentioning
confidence: 85%
“…An insulin tolerance test was performed at the end of the study period "0" (without insulin), 5,10,15,20,25, and 30 minutes after an intraperitoneal injection of insulin (2 U/kg). Body and epididymal adipose tissue were weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the following: (i) hypertension (Liu et al 2005;Dolinsky et al 2009;Thandapilly et al 2010;Toklu et al 2010;Wojciechowski et al 2010;Chan et al 2011;Rimbaud et al 2011); (ii) obesity (Louis et al 2011;Qin et al 2012 (Barger et al 2008). There is also one study that reported cardioprotection in an animal model of heart failure (Tanno et al 2010).…”
mentioning
confidence: 99%